Comparative performance of Cerebral Perfusion Ratio as compared to MCA PI and UA PI in prediction of adverse perinatal outcomes in intra uterine growth restricted fetuses - Shinde, Jyotsna S.; Manmohan, Madan P.; Pasoria, Sanjay S.; Ummer, Thahir V. (International Journal of Research in Medical Sciences, 2019)
Background: Intra uterine growth restriction (IUGR) is a common clinical sign seen due to chronic foetal hypoxemia and is considered a major contributor of perinatal morbidity and mortality. The aim of the present study was to determine and compare the sensitivity and specificity of umbilical artery pulsatility index (UA PI), middle cerebral artery (MCA) PI and cerebral perfusion ratio (CPR) in predicting adverse and poor perinatal outcomes in fetuses with IUGR. Methods: The study included 100 pregnant women with post 24 weeks of gestation with clinical history of IUGR. Doppler examination parameters, including waveforms and measurements, of the umbilical artery, middle cerebral artery were recorded. The Cerebral Perfusion Ratio (CPR) was calculated from MCA PI and UA PI and a final comparison of accuracy of Doppler indices was done with perinatal outcome. Results: The sensitivity of the UA PI was higher (49.3%) than that of the MCA PI (43.6%) and the CPR (37.7%). The specificity of the CPR was higher (87.1%) than that of the MCA PI (83.9%) and the UA PI (74.2%). Conclusions: From the findings of the study, it can be concluded that UA PI is the most sensitive and CPR is the most specific parameter in predicting adverse perinatal outcomes in IUGR fetuses. Thus, in addition to pulsatility indices, CPR should be used as a tool for surveillance and included in the routine reporting formats of obstetric Doppler studies.